Can someone please tell if i am doing this right! Please!

x + Y = 6

2x + y =8

2x + y = 8

x + y = 6

x = -y + 6

2 (-y + 6) + y = 8

2y + 12 + y = 8

3y + 12 = 8

3y = - 4

y = -4/3

X = -y + 6

X = -(-4/3) + 6

x = 4/3 + 6

x = 4/3 + 6

{( 12, 4/3 +6 )}

5 posts
• Page **1** of **1**

Can someone please tell if i am doing this right! Please!

x + Y = 6

2x + y =8

2x + y = 8

x + y = 6

x = -y + 6

2 (-y + 6) + y = 8

2y + 12 + y = 8

3y + 12 = 8

3y = - 4

y = -4/3

X = -y + 6

X = -(-4/3) + 6

x = 4/3 + 6

x = 4/3 + 6

{( 12, 4/3 +6 )}

x + Y = 6

2x + y =8

2x + y = 8

x + y = 6

x = -y + 6

2 (-y + 6) + y = 8

2y + 12 + y = 8

3y + 12 = 8

3y = - 4

y = -4/3

X = -y + 6

X = -(-4/3) + 6

x = 4/3 + 6

x = 4/3 + 6

{( 12, 4/3 +6 )}

Last edited by illuminati58 on Tue Jul 14, 2009 5:27 pm, edited 1 time in total.

- illuminati58
**Posts:**9**Joined:**Sun Jul 12, 2009 11:23 pm

Sorry it was a typo but my answer doesnt seem correct

x + Y = 6

2x + y =8

2x + y = 8

x + y = 6

x = -y + 6

2 (-y + 6) + y = 8

2y + 12 + y = 8

3y + 12 = 8

3y = - 4

y = -4/3

X = -y + 6

X = -(-4/3) + 6

x = 4/3 + 6

x = 4/3 + 6

{( 12, 4/3 +6 )}

x + Y = 6

2x + y =8

2x + y = 8

x + y = 6

x = -y + 6

2 (-y + 6) + y = 8

2y + 12 + y = 8

3y + 12 = 8

3y = - 4

y = -4/3

X = -y + 6

X = -(-4/3) + 6

x = 4/3 + 6

x = 4/3 + 6

{( 12, 4/3 +6 )}

- illuminati58
**Posts:**9**Joined:**Sun Jul 12, 2009 11:23 pm

What about this solution for the same problem?

x + y = 6

2x + y = 8

x= -y + 6

2(-y+6) + y = 8

- 2y -12 + y = 8

y - 12 = 8

y = 16

x = -y + 6

x = (-16) + 6

x = 16 + 6

x = 22

{(22, 16)}

x + y = 6

2x + y = 8

x= -y + 6

2(-y+6) + y = 8

- 2y -12 + y = 8

y - 12 = 8

y = 16

x = -y + 6

x = (-16) + 6

x = 16 + 6

x = 22

{(22, 16)}

- illuminati58
**Posts:**9**Joined:**Sun Jul 12, 2009 11:23 pm

5 posts
• Page **1** of **1**